A systematic approach to the monitoring of normative-legal acts in Ukraine - Onyshchuk, Igor (Journal of the Belarusian State University. Law, 2019)
The essence of system approach to legal monitoring in Ukraine is considered. Arguments that the study of questions of legal monitoring involves the use of one of the newest fundamental approaches – system and method of system analysis, which is considered as an effective method of legal study objects and processes. It is proved that the system analysis of legal acts in Ukraine must to be the result of synthesis of the system approach and scientific research. During the system analysis of law are taken into account: the type of analysis that determines its content; technical and legal tools; the main parameters of the analysed legal system.
Keywords: legal monitoring; system approach; system analysis; legislative process; legal regulation; legal act